Kudüs’te Bir Vakıf Mahalle: Sekiz Yüz Yıllık Meğâribe Mahallesi ve Serencamı - Güneş, Hasan Hüseyin (Vakıflar Genel Müdürlüğü, 2015)
Bu makalede Kudüs Meğâribe Mahallesi tarihî ve siyasî bir monografi metoduyla değerlendirilmiştir. Mahallenin birkaç yönden önemi bulunmaktadır. Bunlar; ı) incelenen mahallenin 800 yılı aşkın bir tarihinin bulunması ıı) bu tarihselliğin yanı sıra kuruluş aşamasında bir Müslüman vakfı olarak tesis edilmesi -ki İslam tarihinde vakıf olarak kurulan başka bir mahalle bulunmamaktadır.- ııı) ilk iki özelliğinin görmezden gelinerek 1967 İsrail işgali esnasında ortadan kaldırılmasıdır. Makalede mahallenin kuruluş sürecine değinildikten sonra kurumları kısaca ele alınmaya çalışılmıştır. Zira 1967 İsrail işgalinde yıkılan ve tahrip edilen müesseselerin sadece evler olmadığı ancak bunlara işaretle mümkündür. Bu kurumların tanıtılması akabinde mahallenin yıkılış sürecine ve bunun arka planına değinilmiştir. Tarihsel ve siyasal süreçler dikkate alınarak Meğâribe mahallesinin günümüz Kudüs’ü için ne anlam ifade ettiğinin altı çizilmiştir.

In this article, the Magarebeh Quarter of Jerusalem is assessed by a historical and political monography method. The quarter is significant in some aspects; it had been existed for over eight hundred years. It is a unique example which was founded as a waqf quarter,being unprecedented throughout the Islamic history. Without considering its importance and such unique aspects, Magarebeh Quarter was terminated by the Israelite occupation of 1967. In this study, after touching on the establishment period of the quarter, its institutions were briefly discussed. Because, it is the only way to show that not only ordinary houses but also the institutions were abolished by Israelite occupation of 1967. Having introduced those institutions, demolishing phase of the district and the negative factors behind it are thouced upon. Considering historical and political processes, the significance of Magarebeh Quarter for Jerusalem has been emphasized in this article. After representation of the processes as historical and political constructions, it is brought to a conclusion that the Quarter of Magarebeh has a deep meaning for also contemporary Jerusalem has to be highlight.
A Waqf Quarter in Jerusalem: The Magarebeh Quarter of Eight Hundred Years And Its Adventure
Keywords: Kudüs; Meğâribe Mahallesi; 1967 Savaşı; Filistin; İsrail; Jerusalem; The Quarter of Magarebeh; The War of 1967; Palestine; Israel